2011
DOI: 10.1016/j.bmc.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis of kinetic solubility measurements of a small molecule library

Abstract: Kinetic solubility measurements using prototypical assay buffer conditions are presented for a ~58,000 member library of small molecules. Analyses of the data based upon physical and calculated properties of each individual molecule were performed and resulting trends were considered in the context of commonly held opinions of how physicochemical properties influence aqueous solubility. We further analyze the data using a decision tree model for solubility prediction and via a multi-dimensional assessment of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 28 publications
(25 reference statements)
2
30
0
Order By: Relevance
“…It is important to remember that an activity cliff, in general, arises due to a key interaction between a specific feature of a small molecule and the receptor. Thus the activity cliff concept and associated analyses cannot be applied to bulk properties such as solubility (although a number of activity cliff‐like cases can be found in large collections of solubility data49). In many cases, these key ligand–receptor interactions can be elucidated via other means, and thus could be used to identify activity cliffs prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to remember that an activity cliff, in general, arises due to a key interaction between a specific feature of a small molecule and the receptor. Thus the activity cliff concept and associated analyses cannot be applied to bulk properties such as solubility (although a number of activity cliff‐like cases can be found in large collections of solubility data49). In many cases, these key ligand–receptor interactions can be elucidated via other means, and thus could be used to identify activity cliffs prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…Using the criteria outlined by Guha et al . 42 , test agents were characterized as exhibiting low aqueous solubility (< 10 μg/mL), medium solubility (10 μg/mL – 60 μg/mL), or high solubility (>60 μg/mL). The solubility result for 4b is presented in Supplementary Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Many examples of such cases can be found in the literature, including cocrystals but also other types of solid mixtures such as inclusion complexes with cyclodextrins (Dua et al, 2011;M Badr-Eldin et al, 2013;Thiry et al, 2017aThiry et al, , 2017b and dispersions with soluble polymers (Brough et al, 2015;Choi and Park, 2017;Ibrahim et al, 2010;Maggi et al, 2013;Six et al, 2004;Thiry et al, 2017a). Noteworthy, Guha et al, (2011), found that APIs can be classified in terms of their kinetic solubility values using different hydrophilicity indices. Hence, all three molecular descriptors identified during screening procedure are related to differences in the polarity of cocrystals components.…”
Section: Selection Of Appropriate Molecular Descriptormentioning
confidence: 99%